VALIDITY AND RELIABILITY MARITIME ENGLISH SEAFARERS PROFICIENCY TEST - Andesvan Gumay (INFERENCE: Journal of English Language Teaching, 2020)
This research goal was to determine the validity and reliability of the Maritime English proficiency test conducted by PUKP 02 in Banten Merchant Marine Polytechnic. The questions were given in the form of multiple choices. This research is categorized as descriptive analysis because it is intended to describe the level of difficulty, distraction power, validity, and reliability of the Maritime English test for third-grade students in the Maritime vocational school in the 2019/2020 academic year by analyzing the validity and reliability of each item. This study concludes: 1) The Validity for the nautical studies there were 43 item items or 71.66% of the total were valid. In the Engineering studies, there are 41 items or 68.33% of the total were valid. 2) The nautical reliability was found to be 0.5968, while for the technical department of 0.6789, the figures were at intervals of 0.40 to 0.70 with moderate interpretation. Thus, it can be concluded that the Maritime English proficiency test has sufficient validity and reliability.